Foundation Legalization Process to The Kemenkumham based on Law No. 28 of 2004 Concerning Amendments to Law No. 16 of 2001 Concerning Foundations (Case Study on The Nurul Hasan Shodiq Foundation) - Moh. Mutawalli Syarowi (Proceeding International Conference Restructuring and Transforming Law, 2023)
Many Al‐Qur'an Education Parks in Indonesia have been running, but quite a lot still do not have a strong legal entity by registering the legal entity of the Foundation with the Ministry of Law and Human Rights, as is the case at TPQ Nurul Hasan in Balapulang village, Tegal Kanupaten, which has existed since 1993. During his TPQ education, Nurul Hasan only relied on personal funds. This research is the Nurul Hasan Shodiq Foundation registering the Foundation's legal entity with the Ministry of Law and Human Rights in accordance with the regulations of Law no. 28 of 2004. This research is a type of qualitative research with a normative juridical approach method. This research is descriptive in nature and aims to describe and analyze systematically, factually and accurately the facts and relationships of existing phenomena. data collection techniques in the form of library research according to the research theme. The law imposes obligations on educational foundations that are legal entities and have been registered as a process for establishing educational foundations because there are no facts about the establishment of educational foundations which have the impact of not receiving School Operational Assistance Funds and other assistance to the government. Therefore, steps or conditions are needed so that it can fulfill the establishment of a foundation in the education sector. Legality has been completed in the legal deed and the decree of the Ministry of Law and Human Rights regarding the establishment of the Nurul Hasan Shodiq Foundation. It is hoped that it can realize Qur'an education at TPQ Nurul Hasan that is advanced and provides prosperity by improving the quality of education.